Synthesis and characterization of molecular probes for various enzymes - An, Chao (My University, 2025)
Enzymes are the cell’s precision machinery, translating molecular recognition into chemistry that governs genome maintenance, signaling, metabolism, immunity, and materials turnover. Because small shifts in their activity can cascade into system-level outcomes, enzymes are both mechanistic readouts and therapeutic entry points. Molecular probes turn that duality into experiments: they bind the right target, reach the right compartment, and report in a way that answers a concrete question. This dissertation integrates synthesis and characterization to build molecular probes and use them to interrogate distinct enzyme classes. Chapter 1 frames scientific motivation and organizational logic. Because the target enzymes differ in fold, chemistry, and biological context, a single modality cannot answer all questions, the work is organized into the following four application-focused chapters: Chapter 2 develops heterobifunctional degraders against the N-terminal methyltransferase NTMT1. Following the canonical PROTAC design, a protein of interested ligand is linked to an E3 ligase recruiter to form productive ternary complexes that drive ubiquitination and proteasomal clearance. A focused 2.45 series establishes linker geometry as the controlling variable: in HEK293FT cells, selected members (2.45I– K) produce time-dependent depletion of NTMT1, whereas closely related analogs (2.45G–H) trigger cytotoxicity—an instructive reminder that permeability, polarity, and off- target degradation are finely balanced. These data validate NTMT1 degradability and map a practical route for optimization. Chapter 3 repurposes Thioglo-1 as an active-site probe and inhibitor for Class I PHA synthases (PhaC_Re, PhaC_Cc, PhaC_Cs). Under harmonized assays, Thioglo-1 shows clear, dose- and time-dependent inhibition of PhaC_Cc and PhaC_Re, but not PhaC_Cs. Divergence likely reflects differences in active-site accessibility or CAP-domain dynamics and positions Thioglo-1 as a selective tool to rank active-site exposure across homologs and to track covalent blockade during polymerization. Chapter 4 addresses materials access for heme-enzyme engineering by providing a concise, high-yield synthesis of N[superscript delta] -methyl-histidine (NMH). Installing a sulfonamide (N– SO₂Ph) on Boc-His-OMe enables MeOTf-mediated, regioselective N[superscript delta] -methylation, followed by basic advance and acid deprotection to deliver NMH in >95% HPLC purity. Ready availability of NMH lowers the barrier to tuning Fe–His coordination and reshaping the “push–pull” landscape in heme catalysis. Chapter 5 delivers a practical synthesis and purification of Z-Gly-Arg-thiobenzyl ester, a staple chromogenic substrate for trypsin-like complement proteases (C1r/C1s). An initial route failed due to thioester lability under piperidine deprotection; the optimized sequence installs SBzl last and couples strategic work-ups with preparative HPLC to obtain a single, stable product. Together, these chapters underscore a single principle: when synthesis is aligned with the biological question, molecular probes become decisive tools—enabling targeted degradation, covalent mapping of active sites, electronic tuning of metalloenzymes, and reliable enzymatic assays that generalize beyond a single system.
Keywords: Molecular probes; PROTAC; NTMT1; Z-Gly-Arg-Thiobenzyl ester